Fundo Amazônia: avanços e dificuldades da participação indígena por via do terceiro setor - Jongh Filho, Louis Philippe Patrick de (2021)
This study aims to analyze the Third Sector performance in the Amazon Fund’s projects that included indigenous peoples among its beneficiaries. There is still a paucity of literature on indigenous participation as well as on indigenous and indigenists associations. Considering that between 2008 and 2021 29 projects were or are being implemented to the benefit of indigenous peoples, the relevance of this REDD+ mechanism to indigenous peoples as well as to development, and to indigenous participation, justify the current analysis. For the purposes of the research approach, a qualitative approach is adopted. As a method for procedure, documents and also the specialized literature are scrutinized, especially meeting minutes and the Amazon Fund’s legislation; public consultations through the Fala.BR online platform (Integrated Ombudsman Platform and Access to Information); as a data collection technique, semistructured interviews are conducted with Third Sector’s project coordinators. As an aid to interpret the data, the content analysis method is used. The analysis on the indigenous participation is focused on the meetings held by the Guidance Committee for the Amazon Fund (COFA); on the role played by the indigenous, indigenist and environmental NGOs; on the implementation of projects with indigenous peoples beneficiaries; and on how the participation has worked taking into account, among others, the Brazilian Policy for Territorial and Environmental Management of Indigenous Lands (PNGATI). The general objective of this master’s thesis is to analyze how the indigenous participation has influenced the functioning of the Amazon Fund regarding to the governance and to the establishment of mechanisms for sustainable development. The specific objectives include a literature review of the International Cooperation for Development (ICD) carried out between developed and developing countries in the environmental field, including the indigenous people’s performance; the analysis of the construction and the operation of the Amazon Fund; understanding the barriers in the Amazon Fund’s governance as regards to indigenous peoples, and identifying the contributions made by indigenous peoples on the projects implemented by the Amazon Fund; characterizing the Amazon Fund’s alternatives to the current development’s model highlighted by the projects implemented by the Third Sector to the benefit of indigenous peoples, both in the elaboration as well as in the implementation of those projects. It can be concluded from the information reviewed that the indigenous participation has influenced the governance of the Amazon Fund in different ways, both as regards to the functioning of the Amazon Fund as well as in respect of the substance of the projects analyzed.